PERBEDAAN PENGETAHUAN DAN SIKAP CUCI TANGAN PAKAI SABUN MENGGUNAKAN MEDIA EDUKASI VIDEO PADA MURID KELAS IV DAN V SD NEGERI 35 PARAK KARAKAH PADANG - Khairunnisa, Azizah; Widdefrita, Widdefrita; Sidiq, Rapitos; Silaban , Evi; Amos, John (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2023)
Clean and Healthy Lifestyle is one of the programs designed by the government. WHO states that can reduce diarrhea rates by up to 47%. However, only 40% of fourth grade and fifth grade elementary school students wash their hands before and before eating when told by the teacher. This is a problem that researchers are looking at. So the purpose of this study was to determine the differences in students' knowledge and attitudes using educational video media at elementary school 35 Parak Karakah Padang. This study used a quantitative method with a descriptive research design. The instrument used in this study was a questionnaire. The sampling technique used in this study was total sampling which involved all fourth and fifth grade elementary school students who were involved in the study. The number of students involved in this study were 80 students. The study was conducted for one week. The type of research was Quasi Experiment (quasi-experimental) through the One Group Pretest and Posttest design approach, meaning that the Pretest was carried out before the intervention and the Posttest was given after the intervention. The research data was processed using SPSS. The average value of knowledge before the intervention was 18.14 and after the intervention was 19.01 with a pvalue of 0.001. Meanwhile, the difference in the average attitude value before the intervention was 40.18 and after the intervention was 42.28 with a p-value of 0.004. The conclusion of this study is the difference in knowledge and attitudes before and before washing hands with soap using video media for fourth and fifth grade students at elementary school 35 Parak Karakah Padang. It is hoped that the results of this study can be used by the public to understand about hand washing with soap, teachers can produce and combine it with other health information.